Material attached with functional material and production method of the same, water cleaner and production method of the same, water cleaner cartridge and production method of the same, air purifier and production method of the same, filter member and production method of the same, support member and production method of the same, expanded polyurethane foam and production method of the same, bottle and production method of the same, container and production method of the same, member composed of cap or lid and production method of the same, material composed of solidified porous carbon material or pulverized material of porous carbon material and binding agent and production method of the same, and porous carbon material and production method of the same
By curing plant-derived materials and carbonizing high-temperature treatment, high-density porous carbon materials are produced, which solves the complexity of transportation and processing and improves production efficiency and material performance.
Patent Information
- Application Number
- JP2024196528
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2017-02-17
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2037-02-21
AI Technical Summary
In the prior art, porous carbon materials produced by powdered rice husks as raw materials have complexity in transportation and treatment, and the carbonization and acid-base treatment efficiency are low, which limits production efficiency.
By curing plant-derived materials at 400°C to 1400°C and carbonized with acid-base treatment, cured porous carbon materials are produced, which improves the density and hardness of the materials and facilitates transportation and processing.
It realizes convenient transportation and treatment of porous carbon materials, improves the efficiency of carbonization and acid-base treatment, and enhances the physical properties of the materials.
Smart Images

Figure 2025020357000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a material having a functional material attached thereto and a method for manufacturing the same, a water purifier and a method for manufacturing the same, a water purifier cartridge and a method for manufacturing the same, an air purifier and a method for manufacturing the same, a filter member and a method for manufacturing the same, a support member and a method for manufacturing the same, a polyurethane foam and a method for manufacturing the same, a bottle and a method for manufacturing the same, a container and a method for manufacturing the same, a member consisting of a cap or lid and a method for manufacturing the same, a material consisting of a solidified porous carbon material or a pulverized product of the porous carbon material and a binder and a method for manufacturing the same, and a porous carbon material and a method for manufacturing the same. [Background technology]
[0002] A porous carbon material made from a plant-derived material and a method for producing the same are known, for example, from Japanese Patent No. 4618308. The method disclosed in this patent publication is for producing a porous carbon material having a specific surface area of 10 m2 or less by the nitrogen BET method. 2 / g or more, and the pore volume by the BJH method and the MP method is 0.1 cm 3 This is a method for producing a porous carbon material having a carbon content of 1000 / g or more, in which a plant-derived material is carbonized at 800°C to 1400°C and then treated with an acid or alkali to remove silicon components from the carbonized plant-derived material. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 4618308 Summary of the Invention [Problem to be solved by the invention]
[0004] The manufacturing methods of the porous carbon material disclosed in the above patent publications are excellent manufacturing methods, but because a type of powdered rice husk is used as a plant-derived material (raw material), the transportation and handling of the raw material and the porous carbon material may be complicated, and the bulk density of the raw material may be low, making it difficult to effectively perform carbonization treatment or acid or alkali treatment. Furthermore, the amount of material that can be processed at one time during production may be limited due to the manufacturing equipment.
[0005] Therefore, an object of the present disclosure is to provide a porous carbon material and a method for producing the same that facilitate the transportation and handling of raw materials and porous carbon materials, the carbonization treatment, and the treatment with acid or alkali. [Means for solving the problem]
[0006] The solidified porous carbon material of the present disclosure for achieving the above object is made from a plant-derived material, and the bulk density of the solidified porous carbon material is 0.2 g / cm 3 ~0.4 grams / cm 3 , preferably 0.3 g / cm 3 ~0.4 grams / cm 3 and the breaking hardness is 20N or more.
[0007] In order to achieve the above object, the method for producing a solidified porous carbon material of the present disclosure includes solidifying a plant-derived material, carbonizing the solidified material at 400°C to 1400°C, and then treating the material with an acid or alkali. Effect of the Invention
[0008] Since the porous carbon material of the present disclosure is solidified, the porous carbon material can be transported and handled more easily. In addition, in the method for producing a solidified porous carbon material of the present disclosure, a plant-derived material is solidified, and then, in the solidified state, is carbonized at 400°C to 1400°C, and then is treated with an acid or alkali, so that the raw material and the porous carbon material can be transported and handled, carbonized, and treated with an acid or alkali more easily. Note that the effects described in this specification are merely examples and are not limited thereto, and additional effects may be present. [Brief description of the drawings]
[0009] [Figure 1] 1A and 1B are graphs showing the results of measurement of the solidified porous carbon material of Example 1 by mercury intrusion porosimetry. [Diagram 2] 2A and 2B are graphs showing the results of measurement of various materials in Comparative Example 1 by mercury porosimetry. [Diagram 3] 3A and 3B are graphs showing the cumulative pore volume values in the range of 0.05 μm to 5 μm obtained by mercury intrusion porosimetry for the solidified porous carbon material of Example 1 and various materials of Comparative Example 1. [Figure 4] FIG. 4 is a schematic cross-sectional view of the water purifier of the second embodiment. [Diagram 5] 5A and 5B are a schematic partial cross-sectional view and a schematic cross-sectional view of a bottle in Example 2. FIG. [Figure 6] 6A and 6B are a schematic partial cross-sectional view and a partially cut-away schematic surface of a modified example of the bottle in Example 2. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the present disclosure will be described based on examples with reference to the drawings, but the present disclosure is not limited to the examples, and various numerical values and materials in the examples are merely examples. The description will be made in the following order. 1. General Description of the Solidified Porous Carbon Material and Its Manufacturing Method of the Present Disclosure 2. Example 1 (Solidified Porous Carbon Material and Manufacturing Method Thereof of the Present Disclosure) 3. Example 2 (Water Purifier and its Modifications) 4.Other
[0011] <General Description of the Solidified Porous Carbon Material and the Manufacturing Method Thereof of the Present Disclosure> In the method for producing a solidified porous carbon material of the present disclosure, the bulk density of the solidified porous carbon material is 0.2 grams / cm 3 ~0.4 grams / cm 3 , preferably 0.3 g / cm 3 ~0.4 grams / cm 3 The cumulative pore volume in the pore size range of 0.05 μm to 5 μm based on mercury intrusion porosimetry is 0.4 cm per gram of the solidified porous carbon material. 3 ~1.2cm 3 , preferably 0.5 cm 3 ~1.0cm 3 The present invention can be in the form of:
[0012] Furthermore, in the solidified porous carbon material of the present disclosure including the above-mentioned preferred embodiment or the solidified porous carbon material obtained by the manufacturing method thereof, the cumulative pore volume value in the pore size range of 10 μm or less based on mercury intrusion porosimetry is 0.7 cm per gram of the solidified porous carbon material. 3 ~2.0cm 3 , preferably 0.7 cm 3 ~1.7cm 3 The present invention can be in the form of:
[0013] Furthermore, in the solidified porous carbon material of the present disclosure including the various preferred embodiments described above or the solidified porous carbon material obtained by the production method thereof, the value of the pore volume based on the BJH method is 3 Per 0.1cm 3 The above-mentioned embodiment may be adopted.
[0014] Furthermore, in the solidified porous carbon material of the present disclosure including the various preferred embodiments described above or the solidified porous carbon material obtained by the production method thereof, the value of the pore volume based on the MP method is 3 Per 0.04cm 3 ~0.1cm 3 The present invention can be in the form of:
[0015] Furthermore, in the solidified porous carbon material of the present disclosure including the various preferred embodiments described above or the solidified porous carbon material obtained by the production method thereof, the value of the pore volume based on the BJH method is 0.3 cm per gram of the solidified porous carbon material. 3 The pore volume based on the MP method is 0.1 cm per gram of the solidified porous carbon material. 3 The above-mentioned embodiment may be adopted.
[0016] Furthermore, in the method for producing a solidified porous carbon material of the present disclosure, including the various preferred embodiments described above, the bulk density of the solidified plant-derived material is 0.2 g / cm 3 to 1.4 grams / cm 3 The present invention can be in the form of:
[0017] Furthermore, in the method for producing a solidified porous carbon material according to the present disclosure, including the various preferred embodiments described above, the bulk density of the material carbonized in a solidified state (hereinafter, sometimes referred to as a "porous carbon material precursor") is 0.2 g / cm 3 Up to 0.8 grams / cm 3 The present invention can be in the form of:
[0018] Furthermore, in the method for producing a solidified porous carbon material of the present disclosure, including the various preferred embodiments described above, starch or potato starch may be used as a binder when the plant-derived material is solidified. Alternatively, the binder may be appropriately selected from materials that do not decompose even when temperatures of room temperature to 180° C. are applied when the plant-derived material is solidified, and that are burned when the plant-derived material is carbonized at 400° C. to 1400° C. The plant-derived material and the binder may be mixed using an appropriate mixer.
[0019] Furthermore, in the solidified porous carbon material of the present disclosure including the various preferred embodiments described above, the ignition residue of the solidified porous carbon material may be 0.1 mass% or more and 20 mass% or less, and in the manufacturing method of the solidified porous carbon material of the present disclosure including the various preferred embodiments described above, the ignition residue of the solidified porous carbon material may be 0.1 mass% or more and 20 mass% or less, preferably 0.1 mass% or more and 15 mass% or less, and more preferably 0.1 mass% or more and 2 mass% or less, by treating with an acid or alkali. The ignition residue is determined according to JIS K1474:20 Measurements can be made based on the "Activated Carbon Test Method" in 14.
[0020] Furthermore, in the solidified porous carbon material of the present disclosure including the various preferred embodiments described above, the ignition residue bulk density of the solidified porous carbon material is 1×10 -4 Grams / cm 3 〜1×10 -1 Grams / cm 3 , preferably 1 x 10 -2 Grams / cm 3 〜1×10 -1 Grams / cm 3 In the method for producing a solidified porous carbon material according to the present disclosure, including the various preferred embodiments described above, the ignition residue bulk density of the carbonized material in a solidified state (porous carbon material precursor) can be 0.1 g / cm. 3The bulk density of the ignition residue of the solidified porous carbon material is 1×10 -4 Grams / cm 3 〜1×10 -1 Grams / cm 3 , preferably 1 x 10 -2 Grams / cm 3 〜1×10 -1 Grams / cm 3 The present invention can be in the form of:
[0021] Furthermore, the breaking hardness of the solidified porous carbon material of the present disclosure including the various preferred embodiments described above is preferably 20 N or more. The breaking hardness of the solidified porous carbon material can be determined using a Kiya hardness tester (manufactured by Fujiwara Seisakusho Co., Ltd.: product number: 043019-C; the same applies below). Specifically, the breaking hardness of 10 samples is measured, the top 3 samples and the bottom 3 samples are excluded, and the breaking hardness is derived from the average value (rounded off to the nearest whole number) of the middle 4 samples.
[0022] In the solidified porous carbon material or the manufacturing method thereof according to the present disclosure including the various preferred forms described above (hereinafter, these may be collectively referred to simply as "the present disclosure"), the porous carbon material is made from a plant-derived material. Here, examples of plant-derived materials include rice (rice), barley, wheat, rye, barnyard millet, foxtail millet, etc., rice husks and straw, coffee beans, tea leaves (e.g., leaves of green tea and black tea), sugar cane (more specifically, sugar cane pomace), corn (more specifically, corn cobs), fruit peels (e.g., citrus peels such as orange peels, grapefruit peels, and mandarin peels, banana peels, etc.), or reeds and wakame stems, but are not limited thereto. Examples of plant-derived materials include vascular plants, ferns, mosses, algae, and seaweeds that grow on land. These materials may be used alone as raw materials, or multiple types may be mixed together. Furthermore, a plant-derived material (for convenience, referred to as "material-A") may be mixed with a material such as seed shells, such as coconut shells and walnut shells, or woody sawdust, such as cedar, pine, and bamboo (for convenience, referred to as "material-B"). In this case, the mixing ratio of material-A to material-B is, for example, based on mass: It is preferable that the ratio is 0.1≦(material-B) / (material-A)≦10, but this is not limited to the mass ratio. The shape and form of the plant-derived material are not particularly limited, and may be, for example, rice husk or straw itself, or a dried product. Furthermore, in the processing of food and beverages such as beer and Western alcohol, products that have been subjected to various processes such as fermentation, roasting, and extraction can also be used. In particular, from the viewpoint of recycling industrial waste, it is preferable to use straw and rice husks that have been processed by threshing, etc. These processed straw and rice husks can be easily obtained in large quantities from, for example, agricultural cooperatives, alcoholic beverage manufacturers, food companies, and food processing companies.
[0023] In addition, before solidification, the plant-derived material may be crushed to a desired particle size or may be classified as desired. The plant-derived material may be washed in advance. The porous carbon material precursor may be coarsely crushed to a desired particle size or may be classified. The solidified porous carbon material of the present disclosure may be crushed to a desired particle size or may be classified, and such crushed or classified products may be applied to various products.
[0024] In the manufacturing method of the solidified porous carbon material of the present disclosure (hereinafter, sometimes simply referred to as "the manufacturing method of the porous carbon material of the present disclosure"), examples of the method for solidifying the plant-derived material include a method of forming into pellets using a molding machine of the ring die type, flat die type, or screw type. There is also a method of solidifying into a firewood-like or roll-like shape. After solidifying by these methods, it may be crushed to an appropriate size. In addition, examples of the shape of the solidified porous carbon material in the present disclosure include a pellet-like shape (more specifically, a cylindrical shape with a diameter of about 2 mm to 15 mm and a length of about 10 mm to 60 mm), a firewood-like shape (more specifically, a shape represented by the product name Momigalite (registered trademark), a diameter of about 50 mm, a central hole of about 15 mm, and a length of, for example, about 30 cm), and a coil-like shape (a shape with a diameter of about 50 mm, a central hole of about 25 mm, a width of about 20 mm, and a length of about 30 cm), and these can also be crushed into granular shapes (diameter: 0.5 mm to 50 mm).
[0025] In the method for producing a porous carbon material of the present disclosure, a step of performing an activation treatment after the acid treatment or alkali treatment may be included, or an activation treatment may be performed after the activation treatment. In the method for producing a porous carbon material of the present disclosure including such a preferred embodiment, the plant-derived material may be subjected to a heat treatment (pre-carbonization treatment) in an oxygen-blocked state at a temperature lower than the carbonization temperature (for example, 400°C to 700°C) before carbonization of the solidified plant-derived material, depending on the plant-derived material used. This makes it possible to extract tar components that will be generated in the carbonization process, and as a result, the tar components that will be generated in the carbonization process can be reduced or removed. The state in which oxygen is blocked can be achieved, for example, by creating an inert gas atmosphere such as nitrogen gas or argon gas, or by creating a vacuum atmosphere, or by putting the plant-derived material into a kind of steam-baked state. In the method for producing a porous carbon material of the present disclosure, depending on the plant-derived material used, in some cases, in order to reduce mineral components and moisture contained in the plant-derived material and to prevent the generation of unpleasant odors during the carbonization process, the solidified plant-derived material may be immersed in an acid or alkali, or in alcohol (e.g., methyl alcohol, ethyl alcohol, isopropyl alcohol). In addition, when treating with an acid, it is possible to remove mineral components contained in the porous carbon material precursor by treating with an inorganic acid such as hydrochloric acid, nitric acid, or sulfuric acid. In addition, in the method for producing a porous carbon material of the present disclosure, a preliminary carbonization treatment may be performed thereafter. Examples of materials that are preferably subjected to a heat treatment in an inert gas include plants that generate a lot of wood vinegar (tar and light oil). Examples of materials that are preferably subjected to a pretreatment with alcohol or the like include seaweeds that contain a lot of iodine and various minerals.
[0026] In the method for producing a porous carbon material according to the present disclosure, a plant-derived material is carbonized at 400°C to 1400°C. Carbonization generally means converting an organic substance (in the case of the solidified porous carbon material according to the present disclosure, the solidified plant-derived material) into a carbonaceous substance by heat treatment (see, for example, JIS M0104-1984). The atmosphere for carbonization may be an atmosphere in which oxygen is blocked, specifically, a vacuum atmosphere, an inert gas atmosphere such as nitrogen gas or argon gas, or an atmosphere in which the plant-derived material is in a kind of steam-baked state. The heating rate up to the carbonization temperature is not limited, but may be 1°C / min or more, preferably 3°C / min or more, more preferably 5°C / min or more under the above atmosphere. The upper limit of the carbonization time may be 10 hours, preferably 7 hours, more preferably 5 hours, but is not limited thereto. The lower limit of the carbonization time may be a time that ensures that the plant-derived material is carbonized. The finally obtained porous carbon material may be subjected to a sterilization treatment. There is no limitation on the type, configuration, and structure of the furnace used for carbonization, and it can be a continuous furnace or a batch furnace.
[0027] In the method for producing a porous carbon material according to the present disclosure, as described above, by carrying out an activation treatment, it is possible to increase the number of micropores having a pore size smaller than 2 nm. Examples of the activation treatment method include a gas activation method and a chemical activation method. Here, the gas activation method is a method in which oxygen, water vapor, carbon dioxide, air, or the like is used as an activator, and the porous carbon material is heated in a gas atmosphere at 700°C to 1400°C, preferably at 700°C to 1000°C, more preferably at 800°C to 1000°C, for several tens of minutes to several hours, thereby developing a microstructure by volatile components and carbon molecules in the porous carbon material. More specifically, the heating temperature may be appropriately selected based on the type of plant-derived material, the type and concentration of gas, and the like, and is more preferably 800°C to 950°C. The chemical activation method is a method in which activation is carried out using sodium hydroxide, potassium hydroxide, zinc chloride, iron chloride, calcium phosphate, calcium hydroxide, magnesium carbonate, potassium carbonate, sulfuric acid, etc. instead of the oxygen or water vapor used in the gas activation method, followed by washing with hydrochloric acid, adjusting the pH with an alkaline aqueous solution, and drying.
[0028] The surface of the solidified porous carbon material of the present disclosure (hereinafter, sometimes simply referred to as the "porous carbon material of the present disclosure") may be subjected to a chemical treatment or molecular modification. An example of the chemical treatment is a treatment in which a carboxy group is generated on the surface by a nitric acid treatment. In addition, various functional groups such as hydroxyl groups, carboxyl groups, ketone groups, ester groups, etc. can be generated on the surface of the porous carbon material of the present disclosure by carrying out a treatment similar to the activation treatment using water vapor, oxygen, alkali, etc. Furthermore, molecular modification is also possible by chemically reacting the porous carbon material of the present disclosure with a chemical species or protein having a reactive hydroxyl group, carboxyl group, amino group, etc.
[0029] In the method for producing a porous carbon material according to the present disclosure, silicon components are removed from the plant-derived material after carbonization by acid treatment or alkali treatment. Here, examples of silicon components include silicon oxides such as silicon dioxide, silicon oxide, and silicon oxide salts. In this manner, by removing the silicon components from the plant-derived material after carbonization, the porous carbon material according to the present disclosure having a high specific surface area can be obtained. In some cases, the silicon components may be removed from the plant-derived material after carbonization by a dry etching method. By removing the silicon components, the value of the ignition residue can be reduced. The value of the ignition residue of the solidified porous carbon material according to the present disclosure is as described above.
[0030] The porous carbon material of the present disclosure has many pores. The pores include "mesopores" with a pore size of 2 nm to 50 nm, "macropores" with a pore size of more than 50 nm, and "micropores" with a pore size of less than 2 nm. Specifically, the mesopores include many pores with a pore size of, for example, 20 nm or less, and in particular many pores with a pore size of 10 nm or less. The micropores include many pores with a pore size of, for example, about 1.9 nm, about 1.5 nm, and about 0.8 nm to 1 nm. In the porous carbon material of the present disclosure, the pore volume measured by the BJH method is 0.3 cm per gram of the porous carbon material of the present disclosure. 3 More than 0.5cm, preferably 0.5cm 3 The pore volume measured by the MP method is preferably 0.1 cm3 or more per gram of the porous carbon material of the present disclosure. 3 More than 0.2 cm, preferably 0.2 cm 3 More than 0.3cm, preferably 0.3cm 3 More than this is desirable.
[0031] In the porous carbon material of the present disclosure, the specific surface area value measured by the nitrogen BET method (hereinafter, sometimes simply referred to as the "specific surface area value") is 10 m per gram of the porous carbon material of the present disclosure in order to obtain even more excellent functionality. 2 More than 50m, preferably 50m 2 More than 100m, preferably 100m 2More preferably, 500m 2 Alternatively, the porous carbon material of the present disclosure may have a thickness of 1 cm or more. 3 Win, 2 x 10 2 m 2 ~3×10 2 m 2 It is desirable that:
[0032] The nitrogen BET method is a method in which an adsorption isotherm is measured by adsorbing and desorbing nitrogen as an adsorbed molecule on an adsorbent (here, a porous carbon material), and the measured data is analyzed based on the BET equation represented by formula (1). Based on this method, the specific surface area, pore volume, etc. can be calculated. Specifically, when calculating the value of the specific surface area by the nitrogen BET method, an adsorption isotherm is first obtained by adsorbing and desorbing nitrogen as an adsorbed molecule on a porous carbon material. Then, from the obtained adsorption isotherm, [p / {V a (p0-p)} is calculated and plotted against the equilibrium relative pressure (p / p0). Then, this plot is regarded as a straight line, and the slope s (=[(C-1) / (C V m )]) and intercept i(=[1 / (C V m Then, from the obtained slope s and intercept i, V is calculated based on equations (2-1) and (2-2). m and C are calculated. Furthermore, V m Based on equation (3), the specific surface area a sBET (See the manual for BELSORP-mini and BELSORP analysis software manufactured by BEL JAPAN, Inc., pages 62 to 66.) This nitrogen BET method is a measurement method conforming to JIS R 1626-1996 "Method of measuring specific surface area of fine ceramic powder by gas adsorption BET method."
[0033] V a =(V m ·C·p) / [(p0-p){1+(C-1)(p / p0)}] (1) [p / {V a (p0-p)}] = [(C-1) / (C V m)](p / p0)+[1 / (C V m )] (1') V m =1 / (s+i) (2-1) C = (s / i) + 1 (2-2) a sBET =(V m ·L·σ) / 22414 (3)
[0034] however, V a :Adsorption amount V m : Monolayer adsorption amount p: Nitrogen equilibrium pressure p0: Saturated vapor pressure of nitrogen L: Avogadro's number σ : Nitrogen adsorption cross section It is.
[0035] When calculating the pore volume Vp by the nitrogen BET method, for example, the adsorption data of the obtained adsorption isotherm is linearly interpolated to obtain the adsorption amount V at the relative pressure set as the pore volume calculation relative pressure. The pore volume Vp can be calculated from this adsorption amount V based on the formula (4) (see pages 62 to 65 of the manual for BELSORP-mini and BELSORP analysis software manufactured by BEL Japan Co., Ltd.). Hereinafter, the pore volume based on the nitrogen BET method may be simply referred to as "pore volume".
[0036] V p =(V / 22414)×(M g / ρ g ) (4)
[0037] however, V: Adsorption amount at relative pressure M g : Molecular weight of nitrogen ρ g : density of nitrogen It is.
[0038] The pore size of the mesopores can be calculated as the pore distribution from the rate of change in pore volume relative to the pore size, for example, based on the BJH method. The BJH method is a method that is widely used as a pore distribution analysis method. When analyzing the pore distribution based on the BJH method, first, a desorption isotherm is obtained by adsorbing and desorbing nitrogen as an adsorbed molecule to and from a porous carbon material. Then, based on the obtained desorption isotherm, the thickness of the adsorption layer when the adsorbed molecules (e.g., nitrogen) are gradually adsorbed and desorbed from the state in which the pores are filled with the adsorbed molecules, and the inner diameter (twice the core radius) of the pores generated at that time are calculated, and the pore radius r is calculated based on the formula (5). p The pore volume is calculated based on the formula (6). The pore diameter (2r p ) to the pore volume change rate (dV p / dr p ) to obtain a pore size distribution curve (see pages 85 to 88 of the manual for BELSORP-mini and BELSORP analysis software manufactured by BEL Japan, Inc.).
[0039] r p =t+r k (5) V pn =R n dV n -R n ·dt n c ΣA pj (6) however, R n =r pn 2 / (r kn -1+dt n ) 2 (7)
[0040] Where: r p : pore radius r k : Pore radius r p The core radius (inner diameter / 2) when an adsorbent layer of thickness t is adsorbed on the inner wall of a pore at that pressure. V pn : Pore volume when the nth nitrogen absorption / desorption occurs dV n: Amount of change at that time dt n t: thickness of the adsorption layer when the nth nitrogen adsorption / desorption occurs n Change in r kn : Core radius at that time c: fixed value r pn : Pore radius when the nth nitrogen absorption / desorption occurs Also, ΣA pj represents the integrated value of the wall area of the pores from j=1 to j=n-1.
[0041] The pore size of the micropores can be calculated as the pore distribution from the pore volume change rate relative to the pore size based on, for example, the MP method. When performing pore distribution analysis using the MP method, first, an adsorption isotherm is obtained by adsorbing nitrogen to a porous carbon material. Then, this adsorption isotherm is converted into a pore volume relative to the thickness t of the adsorption layer (t plot). Then, a pore distribution curve can be obtained based on the curvature of this plot (the amount of change in pore volume relative to the amount of change in the thickness t of the adsorption layer) (see pages 72 to 73 and 82 of the manual for BELSORP-mini and BELSORP analysis software manufactured by BEL Japan Co., Ltd.).
[0042] The measurement of pores by mercury intrusion porosimetry is in accordance with JIS R1655:2003 "Method for testing pore size distribution of molded bodies by mercury intrusion porosimetry for fine ceramics". Specifically, the mercury intrusion measurement was performed using POREMASTER60GT (manufactured by Quantachrome). The pore measurement range was set to 3 nm to 200 μm. The cumulative pore volume can be calculated by accumulating the measured section pore volumes in a desired range. The bulk density can be determined based on the measurement method for packing density described in JIS K1474:2014 "Test method for activated carbon". The ignition residue bulk density can be determined by the product of the bulk density value and the ignition residue value. The ignition residue (residual ash) can be measured based on the measurement method for ignition residue described in JIS K1474:2014 "Test method for activated carbon". It is desirable that the value of the ignition residue (residual ash) in the solidified porous carbon material of the present disclosure is 20 mass% or less, preferably 15 mass% or less. Moreover, it is desirable that the ignition residue (residual ash content) in the porous carbon material precursor is 20% by mass or more, and preferably 25% by mass or more.
[0043] The porous carbon material precursor is treated with an acid or an alkali, and specific examples of the treatment include a method of immersing the porous carbon material precursor in an aqueous solution of an acid or an alkali, and a method of reacting the porous carbon material precursor with an acid or an alkali in a gas phase. More specifically, in the case of the acid treatment, examples of the acid include fluorine compounds exhibiting acidity, such as hydrogen fluoride, hydrofluoric acid, ammonium fluoride, calcium fluoride, and sodium fluoride. When a fluorine compound is used, the amount of fluorine element is four times the amount of silicon element in the silicon component contained in the porous carbon material precursor, and the concentration of the fluorine compound aqueous solution is preferably 10 mass% or more. When the silicon component (e.g., silicon dioxide) contained in the porous carbon material precursor is removed by hydrofluoric acid, silicon dioxide reacts with hydrofluoric acid as shown in chemical formula (A) or chemical formula (B) and is removed as hexafluorosilicic acid (H2SiF6) or silicon tetrafluoride (SiF4), and a porous carbon material can be obtained. Then, washing and drying may be performed.
[0044] SiO2+6HF → H2SiF6+2H2O (A) SiO2+4HF → SiF4+2H2O (B)
[0045] In the case of an alkali treatment using an alkali (base), an example of the alkali is sodium hydroxide. When an aqueous alkali solution is used, the pH of the aqueous solution may be 11 or more. When removing silicon components (e.g., silicon dioxide) contained in the porous carbon material precursor using an aqueous sodium hydroxide solution, the aqueous sodium hydroxide solution is heated to cause silicon dioxide to react as shown in chemical formula (C) and be removed as sodium silicate (Na2SiO3), and a porous carbon material can be obtained. In the case of treating by reacting sodium hydroxide in a gas phase, the solid sodium hydroxide is heated to cause a reaction as shown in chemical formula (C) and be removed as sodium silicate (Na2SiO3), and a porous carbon material can be obtained. After that, washing and drying can be performed.
[0046] SiO2+2NaOH → Na2SiO3+H2O (C)
[0047] A functional material may be attached to the porous carbon material of the present disclosure. Specifically, after performing an acid treatment or an alkali treatment (after performing an activation treatment, if an activation treatment is performed thereafter), a functional material may be attached to the solidified porous carbon material of the present disclosure. Examples of the functional material include agents for more effectively adsorbing the above-mentioned substances present in the air (specifically, for example, ethylene urea, phosphoric acid, copper nitrate), or the functional material may be in a form that exhibits photocatalytic properties. In the latter case, the functional material may be composed of, for example, titanium oxide (TiO2) or zinc oxide (ZnO). By using ethylene urea, formaldehyde and acetaldehyde can be effectively removed, by using phosphoric acid, ammonia can be effectively removed, and by using copper nitrate, ammonia, hydrogen sulfide, etc. can be effectively deodorized. This imparts catalytic properties to the porous carbon material, and the photocatalytic effect allows it to be used as a harmful substance decomposer or harmful substance remover that can be used semi-permanently. Harmful substances can be decomposed and removed by irradiating the porous carbon material with energy rays or electromagnetic waves (e.g., ultraviolet rays, sunlight, visible light, etc.). Harmful substances include those present in the air, and specific examples include various viruses, allergy-causing substances, and carcinogenic substances contained in cigarette smoke (e.g., benzopyrene).
[0048] Although it depends on the type, composition, structure and form of the functional material, the form of adhesion of the functional material to the porous carbon material can include a state in which the functional material adheres to the surface (including inside the pores) of the porous carbon material as fine particles, a state in which the functional material adheres in the form of a thin film, and a state in which the functional material adheres in a sea-island form (when the surface of the porous carbon material is regarded as the "sea", the functional material corresponds to the "islands"). Note that adhesion refers to the adhesion phenomenon between different types of materials. Methods for attaching a functional material to the solidified porous carbon material of the present disclosure include a method in which the porous carbon material is immersed in a solution containing the functional material to deposit the functional material on the surface of the porous carbon material, a method in which the functional material is deposited on the surface of the porous carbon material by electroless plating (chemical plating) or a chemical reduction reaction, a method in which the porous carbon material is immersed in a solution containing a precursor of the functional material and a heat treatment is performed to deposit the functional material on the surface of the porous carbon material, a method in which the porous carbon material is immersed in a solution containing a precursor of the functional material and a ultrasonic treatment is performed to deposit the functional material on the surface of the porous carbon material, and a method in which the porous carbon material is immersed in a solution containing a precursor of the functional material and a sol-gel reaction is performed to deposit the functional material on the surface of the porous carbon material.
[0049] The solidified porous carbon material of the present disclosure can be used, for example, in water purifiers and water purifier cartridges, in air purifiers, and as filter members (air purifier filters and water purifier filters), but the application fields are not limited to these. Alternatively, the material can be used in cosmetics, food, and cigarette filters, composites impregnated with medicines (porous carbon material with an adhesive), and the like.
[0050] For example, in the case of use in a water purifier, the solidified porous carbon material of the present disclosure may be used as a filter material. The solidified porous carbon material may be washed with an acid or alkali to adjust the pH before use. The solidified porous carbon material of the present disclosure can be used to obtain a porous carbon material having a molecular weight of, for example, 1×10 2 〜1×10 5The present invention can remove various substances from water containing the above substances, water containing dodecylbenzenesulfonate, water containing chlorothalonil, water containing dichlorovos, water containing tetracycline, water containing soluble lead, water containing free chlorine, and water containing total organic halogens.
[0051] When used for water purification, air purification, and generally fluid purification, examples of the use form of the solidified porous carbon material of the present disclosure (or, in some cases, a pulverized product) include use in sheet form, use attached to a polyurethane foam, use in a state filled in a column or cartridge, use in a state contained in a water-permeable bag, use in a state formed into a desired shape using a binder (binding agent), and use in powder form. When a substance dispersed in a solution is to be removed, the surface can be treated to be hydrophilic or hydrophobic before use. When used in sheet form, examples of the support member include woven fabric and nonwoven fabric, and examples of the material constituting the support member include cellulose, polypropylene, and polyester. Examples of the form in which the porous carbon material is sandwiched between support members and the form in which the porous carbon material is kneaded into the support member can be mentioned.
[0052] In the water purifier, it may be configured to further have a filtration membrane (for example, a hollow fiber membrane or a flat membrane with holes of 0.4 μm to 0.01 μm) (a combination of the solidified porous carbon material of the present disclosure and a filtration membrane), or it may be configured to further have a reverse osmosis membrane (RO) (a combination of the solidified porous carbon material of the present disclosure and a reverse osmosis membrane), or it may be configured to further have a ceramic filter material (a ceramic filter material having fine holes) (a combination of the solidified porous carbon material of the present disclosure and a ceramic filter material), or it may be configured to further have an ion exchange resin (a combination of the solidified porous carbon material of the present disclosure and an ion exchange resin). In general, filtrate that has passed through a reverse osmosis membrane (RO) contains almost no mineral components, but by passing the filtrate through a reverse osmosis membrane (RO) and then through the solidified porous carbon material of the present disclosure, mineral components can be contained in the filtrate.
[0053] Examples of types of water purifiers include continuous water purifiers, batch water purifiers, and reverse osmosis membrane water purifiers, or faucet-mounted types in which the water purifier body is directly attached to the tip of a water faucet, freestanding types (also called top sink types or tabletop types), faucet-integrated types in which the water purifier is built into the faucet, under-sink types (built-in types) installed in a kitchen sink, pot types (pitcher types) in which the water purifier is built into a container such as a pot or a pitcher, central types directly attached to water piping after the water meter, portable types, and straw types. The configuration and structure of the water purifier can be the same as those of conventional water purifiers. In the water purifier, the solidified porous carbon material of the present disclosure can be used, for example, by being housed in a cartridge, and the cartridge may be provided with a water inlet and a water outlet. The "water" to be purified by a water purifier is not limited to the "water" defined in "3. Terms and definitions" of JIS S3201:2010 "Test methods for household water purifiers."
[0054] Alternatively, examples of members suitable for incorporating the solidified porous carbon material of the present disclosure include caps or lids of bottles (so-called PET bottles) with caps or lids, straw members, or spray members, laminated containers, plastic containers, glass containers, glass bottles, etc. Here, the solidified porous carbon material of the present disclosure is disposed inside the cap or lid, and liquid or water (drinking water, lotion, etc.) in the bottle, laminated container, plastic container, glass container, glass bottle, etc. is passed through the solidified porous carbon material of the present disclosure disposed inside the cap or lid, and then the filtered water can be made to contain mineral components by drinking or using it. Alternatively, a form can be adopted in which a filter medium made of the solidified porous carbon material of the present disclosure is stored in a water-permeable bag, and the bag is placed in liquid or water (drinking water, lotion, etc.) in various containers such as bottles (so-called PET bottles), laminated containers, plastic containers, glass containers, glass bottles, and pot pitchers. EXAMPLES
[0055] Example 1 relates to a solidified porous carbon material and a method for producing the same according to the present disclosure.
[0056] In the manufacturing method of the solidified (specifically, pelletized) porous carbon material of Example 1, rice husks were used as the plant-derived material. The rice husks, which are the plant-derived material, were solidified using a pellet machine, specifically to obtain a solidified plant-derived material in the form of approximately cylindrical pellets with an average diameter of 6 mm and an average length of 30 mm. Note that no binder was used during solidification. The bulk density of the solidified plant-derived material was 0.2 g / cm. 3 to 1.4 grams / cm 3 , specifically, 0.70 g / cm 3 The material in the solidified state was then carbonized at 400 to 1400°C. Specifically, the material was carbonized at 500°C for 3 hours in a nitrogen atmosphere using a mantle heater. The bulk density of the resulting carbonized material in the solidified state (porous carbon material precursor) was 0.2 g / cm. 3 Up to 0.8 grams / cm 3 , specifically, 0.50 g / cm 3 The ignition residue of the carbonized material in the solidified state was 42%, and the ignition residue bulk density was 0.1 g / cm 3 More specifically, 0.50 grams / cm 3 x 0.42 = 0.21 g / cm 3 The fracture hardness was measured using a Kiya hardness tester and found to be 73 N. The solidified, carbonized material was then immersed in a 1 mol / L aqueous solution of sodium hydroxide at 80°C and stirred for 24 hours. It was then washed until it became neutral, and the solidified porous carbon material was filtered and dried at 120°C for 24 hours.
[0057] Then, the solidified porous carbon material was classified using 20 mesh and 200 mesh sieves to obtain the samples shown in Table 1 below. Furthermore, the solidified porous carbon material of Example 1A was subjected to an activation treatment based on the gas activation method, specifically, an activation treatment using steam at 900°C for 2 hours, to obtain Example 1C. The solidified porous carbon material of Example 1B was subjected to an activation treatment based on the gas activation method, specifically, an activation treatment using steam at 900°C for 2 hours and 3 hours, to obtain Examples 1D and 1E. The ignition residue value of the solidified porous carbon material (Example 1A) obtained by treating with an acid or alkali was 0.1 mass% or more and 20 mass% or less, specifically, 9.3 mass%. The breaking hardness of Example 1A was 35N.
[0058] Example 1A: 20 mesh-on product (before steam activation) Example 1B: 20 mesh pass, 200 mesh on (before steam activation) Example 1C: Steam activated product of Example 1A Example 1D: Steam activated product of Example 1B Example 1E: Steam-activated product of Example 1B
[0059] In the production of Examples 1F, 1G, 1H, 1J, 1K, 1L, and 1M, rice husks were used as the plant-derived material. The rice husks, which are the plant-derived material, were solidified using a pellet machine, specifically to obtain a solidified plant-derived material in the form of approximately cylindrical pellets with an average diameter of 6 mm and an average length of 30 mm. Note that no binder was used during solidification. The bulk density of the solidified plant-derived material was 0.2 g / cm. 3 to 1.4 grams / cm 3 , specifically, 0.70 g / cm 3 The solidified material was then carbonized at 400 to 1400°C. However, unlike the above-mentioned sample, the material was carbonized in a muffle furnace under a nitrogen gas atmosphere at 800°C for 1 hour. The bulk density of the resulting carbonized material in a solidified state (porous carbon material precursor) was 0.2 g / cm.3 Up to 0.8 grams / cm 3 , specifically, 0.46 g / cm 3 The ignition residue of the carbonized material in the solidified state was 44%, and the ignition residue bulk density was 0.1 g / cm 3 Specifically, 0.46 grams / cm 3 x 0.44 = 0.20 g / cm 3 The fracture hardness was measured using a Kiya hardness tester and found to be 120 N. The solidified, carbonized material was then immersed in a 1 mol / L aqueous solution of sodium hydroxide at 80°C and stirred for 24 hours. It was then washed until it became neutral, and the solidified porous carbon material was filtered and dried at 120°C for 24 hours.
[0060] Next, the mixture was classified using a sieve to obtain a 3 mm on product, and a 1 mm on product and a 3 mm pass product (referred to as a 1 to 3 mm product). The 3 mm on product was subjected to an activation treatment based on a gas activation method, specifically, an activation treatment using steam at 860°C for 2 hours, to obtain a solidified porous carbon material of Example 1F. Furthermore, the solidified porous carbon material of Example 1F was washed with water and dried at 120°C to obtain a solidified porous carbon material of Example 1G. The 3 mm on product was subjected to an activation treatment using steam at 860°C for 2.5 hours, to obtain a solidified porous carbon material of Example 1H. Furthermore, the solidified porous carbon material of Example 1H was washed with water and dried at 120°C to obtain a solidified porous carbon material of Example 1J. Furthermore, the 3 mm on product was subjected to an activation treatment using steam at 850°C for 3 hours, washed with water, and dried at 120°C to obtain a solidified porous carbon material of Example 1K. On the other hand, the 1-3 mm product was subjected to activation treatment based on a gas activation method, specifically, activation treatment using water vapor at 860°C for 2 hours, to obtain a solidified porous carbon material of Example 1L. The solidified porous carbon material of Example 1L was then washed with water and dried at 120°C to obtain a solidified porous carbon material of Example 1M. The fracture hardness of the obtained Examples 1F, 1G, 1H, 1J, and 1K was measured using a Kiya hardness tester, and the results are shown below.
[0061] Breaking Hardness Example 1F 81N Example 1G 77N Example 1H 66N Example 1J 75N Example 1K 73N
[0062] In the production of Examples 1N, 1P, 1Q, 1R, and 1S, rice husks were used as the plant-derived material. The rice husks, which are the plant-derived material, were solidified using a pellet machine, specifically to obtain a solidified plant-derived material in the form of approximately cylindrical pellets with an average diameter of 6 mm and an average length of 30 mm. Note that no binder was used during solidification. The bulk density of the solidified plant-derived material was 0.2 g / cm. 3 to 1.4 grams / cm 3 , specifically, 0.67 g / cm 3 The material in the solidified state was then carbonized at 400°C to 1400°C. Specifically, the material was carbonized in a nitrogen gas atmosphere at 600°C for 0.5 hours using a rotary kiln. The bulk density of the resulting carbonized material in the solidified state (porous carbon material precursor) was 0.2 g / cm. 3 Up to 0.8 grams / cm 3 , specifically, 0.55 g / cm 3 The ignition residue of the carbonized material in the solidified state was 40%, and the ignition residue bulk density was 0.1 g / cm 3 More specifically, 0.55 grams / cm 3 x 0.40 = 0.22 g / cm 3 It was.
[0063] Next, activation treatment based on the gas activation method, specifically, activation treatment using steam at 850°C for 3.5 hours (Example 1N), 4.0 hours (Example 1P), 4.75 hours (Example 1Q), 5.5 hours (Example 1R), and 5.75 hours (Example 1S), was performed, and then the material was immersed in a 4.0 mol / L, 50°C aqueous potassium hydroxide solution and stirred for 12 hours. Next, the material was washed with hydrochloric acid until it became neutral, and the solidified porous carbon material obtained was filtered and dried at 120°C for 24 hours. The five types of solidified porous carbon materials thus obtained were named Example 1N, Example 1P, Example 1Q, Example 1R, and Example 1S.
[0064] For comparison, unconsolidated rice husks (i.e., rice husks, as is) were carbonized using a mantle heater under nitrogen atmosphere at 500 °C for 3 hours. The bulk density of the resulting unconsolidated material was 0.1 g / cm. 3 The ignition residue was 42% and the ignition residue bulk density was 0.04 g / cm 3 The carbonized material in an unsolidified state was then immersed in a 1 mol / L sodium hydroxide aqueous solution at 80°C and stirred for 24 hours. Next, it was washed until it became neutral, and the unsolidified porous carbon material obtained was filtered and dried at 120°C for 24 hours. Then, it was classified using 20 mesh and 200 mesh sieves to obtain a sample of Comparative Example 1B shown in Table 2 below as a 20 mesh pass, 200 mesh on product. Incidentally, almost no 20 mesh on product was obtained. In addition, unsolidified rice husks (i.e., rice husks in their original state) were carbonized in a self-combustion carbonization furnace. The bulk density of the obtained unsolidified material was 0.11 g / cm 3 The ignition residue was 36%, and the ignition residue bulk density was 0.04 g / cm 3 Then, the mixture was immersed in a 1 mol / L aqueous solution of sodium hydroxide at 80°C and stirred for 24 hours. Next, the mixture was washed until it became neutral, and the obtained unsolidified porous carbon material was filtered and dried at 120°C for 24 hours. Then, the mixture was classified using 20 mesh and 200 mesh sieves to obtain Comparative Example 1C shown in Table 2 below as a 20 mesh pass, 200 mesh on product. Furthermore, the obtained Comparative Example 1C was subjected to activation treatment using water vapor at 900°C for 2 hours and 3 hours to obtain Comparative Example 1D and Comparative Example 1E. In Comparative Examples 1F to 1J, commercially available materials were used. In Reference Examples 1A to 1D, the raw materials were not plant-derived raw materials, so they were listed as reference examples. When the fracture hardness of Comparative Example 1B was measured, it was broken immediately after the start of the test and could not be measured.
[0065] Comparative Example 1B: 20 mesh pass, 200 mesh on Comparative Example 1C: Unsolidified rice husks used as raw material Comparative Example 1D: Steam activated product of Comparative Example 1C Comparative Example 1E: Steam-activated product of Comparative Example 1C Comparative Example 1F: Kuraray Coal GW (60 mesh or more, 30 mesh or less) manufactured by Kuraray Chemical Co., Ltd. Comparative Example 1G: Kuraray Coal GG (60 mesh or more, 30 mesh or less) manufactured by Kuraray Chemical Co., Ltd. Comparative Example 1H: Tsurumi Coal 4GS-S (coconut shell charcoal) Comparative Example 1J: SWKW (wood activated carbon) manufactured by Sanwa Corporation Reference Example 1A: UN 8-32 mesh (coal crushing) manufactured by Union Service Co., Ltd. Reference Example 1B: UP 4-6 mesh (coal pellets) manufactured by Union Service Co., Ltd. Reference Example 1C: Activated carbon, crushed, 2mm to 5mm, manufactured by Wako Pure Chemical Industries, Ltd., vendor code 031-18061 (crushed peat) Reference Example 1D: Activated carbon, powder, neutral, manufactured by Wako Pure Chemical Industries, Ltd., vendor code 035-18101 (peat powder)
[0066] The measured values of various physical properties of Examples 1A to 1E, Comparative Examples 1B to 1J, and Reference Examples 1A to 1D are shown in Table 3 below. In Table 3, "Mercury Porosimetry-A" indicates the cumulative pore volume per gram of solidified porous carbon material in the pore size range of 10 μm or less based on mercury porosimetry, and "Mercury Porosimetry-B" indicates the cumulative pore volume per gram of solidified porous carbon material in the pore size range of 0.05 μm to 5 μm based on mercury porosimetry. Furthermore, "Pore Volume-A" indicates the cumulative pore volume per cm of solidified porous carbon material in the pore size range of 10 μm or less based on mercury porosimetry. 3 The "Pore Volume-B" indicates the cumulative pore volume per cm of a solidified porous carbon material having a pore size range of 0.05 μm to 5 μm based on the mercury intrusion method. 3 The cumulative pore volume per unit area is shown.
[0067] [Table 1]
[0068] <Table 3 (continued)> [Table 2]
[0069] <Table 3 (continued)> [Table 3]
[0070] <Table 3 (continued)> [Table 4]
[0071] From Table 3, in Examples 1A to 1E, the bulk density of the solidified porous carbon material was 0.2 g / cm 3 ~0.4 grams / cm 3 , preferably 0.3 g / cm 3 ~0.4 grams / cm 3 The cumulative pore volume value in the pore size range of 0.05 μm to 5 μm based on the mercury intrusion method (the “Mercury intrusion method-B” value) is 0.4 cm per gram of the solidified porous carbon material. 3 ~1.2cm 3 , preferably 0.5 cm 3 ~1.0cm 3 The cumulative pore volume value for pore sizes of 10 μm or less based on mercury intrusion porosimetry (the "Mercury intrusion porosimetry-A" value) was 0.7 cm per gram of the solidified porous carbon material. 3 ~2.0cm 3 , preferably 0.7 cm 3 ~1.7cm 3 Furthermore, the pore volume value based on the BJH method was 1 cm 3 of the solidified porous carbon material. 3 0.1cm per 3 The pore volume value based on the MP method is calculated as follows for 1 cm of solidified porous carbon material. 3Per 0.04cm 3 ~0.1cm 3 Moreover, the pore volume value based on the BJH method was 0.3 cm per gram of the solidified porous carbon material. 3 The pore volume based on the MP method is 0.1 cm per gram of the solidified porous carbon material. 3 The bulk density of the ignition residue of the solidified porous carbon material was 1×10 -4 Grams / cm 3 〜1×10 -1 Grams / cm 3 , preferably 1 x 10 -2 Grams / cm 3 〜1×10 -1 Grams / cm 3 It was.
[0072] The results of the measurements by the mercury intrusion method are shown in the graphs of Figures 1A, 1B, 2A, and 2B. The graph of Figure 1B is an enlarged view of the left-hand peak portion of the graph of Figure 1A, and the graph of Figure 2B is an enlarged view of the left-hand peak portion of the graph of Figure 2A. The horizontal axes of Figures 1A, 1B, 2A, and 2B represent pore diameter (unit: angstroms), and the vertical axes represent interval pore volume (unit: cm 3 / gram). The peaks on the right side of the graphs in FIG. 1A and FIG. 2A are due to gaps present between the solidified porous carbon materials. Graphs showing the cumulative pore volume values in the range of 0.05 μm to 5 μm obtained by mercury intrusion are shown in FIG. 3A and FIG. 3B. In FIG. 1A, FIG. 1B, and FIG. 3A, "A" indicates the value of Example 1A, "B" indicates the value of Example 1B, "C" indicates the value of Example 1C, "D" indicates the value of Example 1D, and "E" indicates the value of Example 1E, and in FIG. 2A, FIG. 2B, and FIG. 3B, "b" indicates the value of Comparative Example 1B, "c" indicates the value of Comparative Example 1C, "d" indicates the value of Comparative Example 1D, "e" indicates the value of Comparative Example 1E, "f" indicates the value of Comparative Example 1F, and "g" indicates the value of Comparative Example 1G. In FIG. 3B, the value (f) of Comparative Example 1F and the value (g) of Comparative Example 1G overlap.
[0073] The porous carbon materials of Examples 1A to 1E are solidified, compared with the non-solidified porous carbon materials (Comparative Examples 1B to 1E) and activated carbons made from coconut shells (Comparative Examples 1F to 1J), and therefore the porous carbon materials can be transported and handled more easily. In addition, in the method for producing the porous carbon material of Example 1, the plant-derived material is solidified, then carbonized in the solidified state at 400°C to 1400°C, and then treated with an acid or alkali, so that the raw materials and the porous carbon material can be transported, handled, carbonized, and treated with an acid or alkali more easily. Furthermore, since the solidified porous carbon materials of Examples 1A to 1E have the above-mentioned physical property values, compared to the unsolidified porous carbon materials (Comparative Examples 1B to 1E), the surface area per unit volume, the micropore value (pore volume value based on the MP method), and the mesopore value (pore volume value based on the BJH method) are larger, so that the reaction surface and adsorption pores per unit volume are larger, and the materials have excellent advantages in terms of reacting and adsorbing more substances in a limited space, such as air purifier filters and water purifiers. Furthermore, compared to activated carbon made from coconut shells (Comparative Examples 1F to 1H), the ratio of mesopores and macropores is larger, so that diffusion of water, air, and solvents occurs easily inside the porous carbon material, and the reaction rate becomes faster, and the materials have excellent advantages in applications requiring more reactions in a short period of time, such as air purifier filters, water purifier filters, and water purifier cartridges. Furthermore, since the wood activated carbon (Comparative Example 1J) is produced from already crushed sawdust, the product is in the form of a powder. If it is used as a filter for a water purifier or air purifier, the pressure loss will be high, and the material is not suitable for use as a filter for a water purifier or air purifier. EXAMPLES
[0074] In Example 2, an example will be described in which the solidified porous carbon material explained in Examples 1A to 1E is used as a filter medium in a water purifier.
[0075] A cross-sectional view of the water purifier of Example 2 is shown in FIG. 4. The water purifier of Example 2 is a continuous water purifier, and is a faucet-connected water purifier in which the water purifier body is directly attached to the tip of a water faucet. The water purifier of Example 2 includes a water purifier body 10, a first packed section 12 filled with the solidified porous carbon material 11 of Examples 1A to 1E disposed inside the water purifier body 10, and a second packed section 14 filled with cotton 13. Tap water discharged from a water faucet passes through an inlet 15 provided in the water purifier body 10, the porous carbon material 11 and the cotton 13, and is discharged from an outlet 16 provided in the water purifier body 10.
[0076] Alternatively, as shown in a schematic partial cross-sectional view in FIG. 5A, a filter medium 40 (hereinafter, simply referred to as "filter medium 40") made of the solidified porous carbon material described in Examples 1A to 1E can be incorporated into a bottle (so-called PET bottle) 20 with a cap member 30. Specifically, the filter medium 40 is disposed inside the cap member 30, and filters 31, 32 are disposed on the liquid inlet side and liquid outlet side of the cap member 30 so that the filter medium 40 does not flow out. Then, by passing the liquid or water (drinking water, lotion, etc.) 21 in the bottle 20 through the filter medium 40 disposed inside the cap member 30 and drinking or using it, for example, the mineral components in the liquid (water) can be increased. The cap member 30 is usually closed with a lid not shown.
[0077] Alternatively, as shown in a schematic cross-sectional view in FIG. 5B, a filter material 40 may be stored in a water-permeable bag 50, and the bag 50 may be poured into the liquid or water (drinking water, lotion, etc.) 21 in the bottle 20. Reference numeral 22 denotes a cap for closing the mouth of the bottle 20. Alternatively, as shown in a schematic cross-sectional view in FIG. 6A, a filter material 40 may be placed inside a straw member 60, and filters (not shown) may be placed on the liquid inlet side and liquid outlet side of the straw member to prevent the filter material 40 from flowing out. The liquid or water (drinking water) 21 in the bottle 20 may be passed through the filter material 40 placed inside the straw member 60, and the mineral content in the liquid (water) may be increased by drinking it. Alternatively, as shown in a schematic cutaway view in FIG. 6B, a filter material 40 may be placed inside a spray member 70, and filters (not shown) may be placed on the liquid inlet side and liquid outlet side of the spray member 70 to prevent the filter material 40 from flowing out. By pressing the push button 71 provided on the spray member 70, the liquid or water (drinking water, lotion, etc.) 21 in the bottle 20 passes through the filter material 40 arranged inside the spray member 70 and is sprayed from the spray hole 72, thereby increasing the mineral content in the liquid (water).
[0078] Although the present disclosure has been described above based on the preferred embodiments, the present disclosure is not limited to these embodiments and various modifications are possible. The solidified porous carbon material, raw materials (materials derived from plants), manufacturing methods, manufacturing conditions, etc. described in the embodiments are examples and can be changed as appropriate. As the filter material described in Example 2, a water purifier can be made by combining a filter material made of the solidified porous carbon material described in Example 1 with a ceramic filter material (a ceramic filter material having fine holes), or a water purifier can be made by combining a filter material with an ion exchange resin.
[0079] The present disclosure may also be configured as follows. [A01] 《Solidified porous carbon material》 A solidified porous carbon material made from a plant-derived material, The bulk density of the solidified porous carbon material is 0.2 g / cm 3 ~0.4 grams / cm 3 and The cumulative pore volume in the pore size range of 0.05 μm to 5 μm based on mercury intrusion porosimetry is 0.4 cm per gram of solidified porous carbon material. 3 ~1.2cm 3 A solidified porous carbon material. [A02] The cumulative pore volume in the pore size range of 0.05 μm to 5 μm based on the mercury intrusion method is 0.5 cm per gram of the solidified porous carbon material. 3 ~1.0cm 3 The solidified porous carbon material according to [A01], [A03] The cumulative pore volume in the range of pore sizes of 10 μm or less based on mercury intrusion porosimetry is 0.7 cm per gram of solidified porous carbon material. 3 ~2.0cm 3 The solidified porous carbon material according to [A01] or [A02], [A04] The pore volume value based on the BJH method is calculated using 1 cm of solidified porous carbon material. 3 0.1cm per 3 The solidified porous carbon material according to any one of [A01] to [A03] above. [A05] The pore volume value based on the MP method is calculated using 1 cm of solidified porous carbon material. 3 Per 0.04cm 3 ~0.1cm 3 The solidified porous carbon material according to any one of [A01] to [A04], [A06] The pore volume value based on the BJH method is 0.3 cm per gram of solidified porous carbon material. 3 The pore volume based on the MP method is 0.1 cm per gram of the solidified porous carbon material. 3 The solidified porous carbon material according to any one of [A01] to [A05] above. [A07] The solidified porous carbon material according to any one of [A01] to [A06], wherein the ignition residue of the solidified porous carbon material is 0.1 mass % or more and 20 mass % or less. [A08] The bulk density of the ignition residue of the solidified porous carbon material is 1×10 -4 Grams / cm 3 〜1×10 -1 Grams / cm 3 The solidified porous carbon material according to any one of [A01] to [A07], [A09] The solidified porous carbon material according to any one of [A01] to [A08], having a breaking hardness of 20 N or more. [B01] 《Method of manufacturing a porous carbon material》 A method for producing a solidified porous carbon material, comprising solidifying a plant-derived material, carbonizing the solidified material at 400°C to 1400°C, and then treating the solidified material with an acid or alkali. [B02] The bulk density of the solidified porous carbon material is 0.2 g / cm 3 ~0.4 grams / cm 3 and The cumulative pore volume in the pore size range of 0.05 μm to 5 μm based on mercury intrusion porosimetry is 0.4 cm per gram of solidified porous carbon material. 3 ~1.2cm 3 The method for producing a solidified porous carbon material according to [B01], [B03] The bulk density of the solidified plant-based material is less than 0.2 grams / cm 3 to 1.4 grams / cm 3 The method for producing a solidified porous carbon material according to [B01] or [B02], [B04] The bulk density of the carbonized material in the solidified state is less than 0.2 grams / cm 3 Up to 0.8 grams / cm 3 The method for producing a solidified porous carbon material according to any one of [B01] to [B03], [B05] The method for producing a solidified porous carbon material according to any one of [B01] to [B04], wherein starch or potato starch is used as a binder when solidifying a plant-derived material. [B06] The method for producing a solidified porous carbon material according to any one of [B01] to [B05], wherein the ignition residue of the solidified porous carbon material is set to 0.1 mass % or more and 20 mass % or less by treating with an acid or alkali. [B07] The bulk density of the ignition residue of the carbonized material in the solidified state is 0.1 g / cm 3 That's all. The bulk density of the ignition residue of the solidified porous carbon material is 1×10 -4 Grams / cm 3 〜1×10 -1 Grams / cm 3 The method for producing a solidified porous carbon material according to any one of [B01] to [B06], [B08] The cumulative pore volume in the pore size range of 0.05 μm to 5 μm based on the mercury intrusion method is 0.5 cm per gram of the solidified porous carbon material. 3 ~1.0cm 3 The method for producing a solidified porous carbon material according to any one of [B01] to [B07], [B09] The cumulative pore volume in the range of pore sizes of 10 μm or less based on mercury intrusion porosimetry is 0.7 cm per gram of solidified porous carbon material. 3 ~2.0cm 3 The method for producing a solidified porous carbon material according to any one of [B01] to [B08], [B10] The pore volume value based on the BJH method is calculated using 1 cm of solidified porous carbon material. 3 Per 0.1cm 3 The method for producing a solidified porous carbon material according to any one of [B01] to [B09] above. [B11] The pore volume value based on the MP method is calculated as the volume of 1 cm of solidified porous carbon material. 3 Per 0.04cm 3 ~0.1cm 3The method for producing a solidified porous carbon material according to any one of [B01] to [B10], [B12] The pore volume value based on the BJH method is 0.3 cm per gram of solidified porous carbon material. 3 The pore volume based on the MP method is 0.1 cm per gram of the solidified porous carbon material. 3 The method for producing a solidified porous carbon material according to any one of [B01] to [B11] above. [B13] The method for producing a solidified porous carbon material according to any one of [B01] to [B12], wherein the ignition residue of the solidified porous carbon material is 0.1 mass % or more and 20 mass % or less. [B14] The bulk density of the ignition residue of the solidified porous carbon material is 1×10 -4 Grams / cm 3 〜1×10 -1 Grams / cm 3 The method for producing a solidified porous carbon material according to any one of [B01] to [B13], [B15] The method for producing a solidified porous carbon material according to any one of [B01] to [B14], wherein the solidified porous carbon material has a fracture hardness of 20 N or more. [C01] Water Purifier A water purifier comprising: a water purifier body; and a packed part disposed inside the water purifier body and packed with the porous carbon material 11 according to any one of [A01] to [A09]. [Explanation of symbols]
[0080] REFERENCE SIGNS LIST 10 water purifier body, 11 porous carbon material, 12 first filling section, 13 cotton, 14 second filling section, 15 inlet, 16 outlet, 20 bottle, 21 liquid or water, 22 cap, 30 cap member, 31, 32 filter, 40 filter medium, 50 bag, 60 straw member, 70 spray member, 71 push button, 72 spray hole
Claims
1. A solidified porous carbon material, comprising: Porous carbon materials are made from plant-derived materials. The fracture hardness of the solidified porous carbon material is 20 N or more; The ignition residue of the solidified porous carbon material is 0.1 mass % or more and 20 mass % or less, A material having a cumulative pore volume value based on mercury intrusion in the pore size range of 0.05 μm to 5 μm of 0.4 cm 3 to 1.2 cm 3 per gram of solidified porous carbon material.
2. The material according to claim 1, wherein the value of the pore volume based on the BJH method is 0.1 cm 3 or more per cm 3 of the solidified porous carbon material.
3. The material according to claim 1, wherein the solidified porous carbon material has an ignition residue bulk density of 1×10 −4 to 1×10 −1 grams / cm 3 .
4. A support member comprising a solidified porous carbon material, Porous carbon materials are made from plant-derived materials. The fracture hardness of the solidified porous carbon material is 20 N or more; The ignition residue of the solidified porous carbon material is 0.1 mass % or more and 20 mass % or less, A support member having a cumulative pore volume value in the pore size range of 0.05 μm to 5 μm based on mercury intrusion of 0.4 cm 3 to 1.2 cm 3 per gram of solidified porous carbon material.
5. A support member as described in claim 4, wherein the support member sandwiches a porous carbon material.
6. A support member as described in claim 4, wherein a porous carbon material is kneaded into the support member.
7. A support member according to any one of claims 4 to 6, wherein the support member is made of a woven or nonwoven fabric.
8. A support member according to any one of claims 4 to 7, wherein the material constituting the support member is cellulose, polypropylene or polyester.
9. The support member according to claim 4, wherein the pore volume value based on the BJH method is 0.1 cm 3 or more per cm 3 of the solidified porous carbon material.
10. The support member according to claim 4, wherein the solidified porous carbon material has an ignition residue bulk density of 1×10 −4 to 1×10 −1 grams / cm 3 .
11. A material comprising a solidified porous carbon material and a binder, Porous carbon materials are made from plant-derived materials. The fracture hardness of the solidified porous carbon material is 20 N or more; The ignition residue of the solidified porous carbon material is 0.1 mass % or more and 20 mass % or less, A material comprising a porous carbon material and a binder, the cumulative pore volume value in the pore size range of 0.05 μm to 5 μm as determined by mercury intrusion porosimetry being 0.4 cm 3 to 1.2 cm 3 per gram of the solidified porous carbon material.
12. The material according to claim 11, wherein the value of the pore volume based on the BJH method is 0.1 cm 3 or more per cm 3 of the solidified porous carbon material.
13. The material according to claim 11 or 12, wherein the solidified porous carbon material has an ignition residue bulk density of 1×10 −4 to 1×10 −1 grams / cm 3 .
14. A water purifier comprising a solidified porous carbon material, Porous carbon materials are made from plant-derived materials. The fracture hardness of the solidified porous carbon material is 20 N or more; The ignition residue of the solidified porous carbon material is 0.1 mass % or more and 20 mass % or less, A water purifier, wherein the cumulative pore volume in the pore size range of 0.05 μm to 5 μm based on mercury intrusion porosimetry is 0.4 cm 3 to 1.2 cm 3 per gram of the solidified porous carbon material.
15. A water purifier cartridge comprising a solidified porous carbon material, comprising: Porous carbon materials are made from plant-derived materials. The fracture hardness of the solidified porous carbon material is 20 N or more; The ignition residue of the solidified porous carbon material is 0.1 mass % or more and 20 mass % or less, A water purifier cartridge, wherein the cumulative pore volume value in the pore size range of 0.05 μm to 5 μm based on mercury intrusion is 0.4 cm 3 to 1.2 cm 3 per gram of solidified porous carbon material.
16. An air purifier comprising a solidified porous carbon material, Porous carbon materials are made from plant-derived materials. The fracture hardness of the solidified porous carbon material is 20 N or more; The ignition residue of the solidified porous carbon material is 0.1 mass % or more and 20 mass % or less, An air purifier, wherein the cumulative pore volume value in the pore size range of 0.05 μm to 5 μm based on mercury intrusion porosimetry is 0.4 cm 3 to 1.2 cm 3 per gram of the solidified porous carbon material.
17. A filter element comprising a solidified porous carbon material, Porous carbon materials are made from plant-derived materials. The fracture hardness of the solidified porous carbon material is 20 N or more; The ignition residue of the solidified porous carbon material is 0.1 mass % or more and 20 mass % or less, A filter element, wherein the cumulative pore volume in the pore size range of 0.05 μm to 5 μm based on mercury intrusion porosimetry is 0.4 cm 3 to 1.2 cm 3 per gram of the solidified porous carbon material.
18. A method for producing a solidified porous carbon material, comprising the steps of: a solidification step of solidifying the raw plant-derived material; a carbonization step of carbonizing the plant-derived material at 400° C. to 1400° C.; and a treatment step of treating the material carbonized in the carbonization step with an acid or an alkali after the carbonization step. The fracture hardness of the solidified porous carbon material is 20 N or more; The ignition residue of the solidified porous carbon material is 0.1 mass % or more and 20 mass % or less, A method for producing a material, wherein the cumulative pore volume in the pore size range of 0.05 μm to 5 μm based on mercury intrusion is 0.4 cm 3 to 1.2 cm 3 per gram of the solidified porous carbon material.
19. A method for producing a pulverized product of a solidified porous carbon material, comprising the steps of: The fracture hardness of the solidified porous carbon material is 20 N or more; The ignition residue of the solidified porous carbon material is 0.1 mass % or more and 20 mass % or less, The cumulative pore volume in the pore size range of 0.05 μm to 5 μm based on mercury intrusion porosimetry is 0.4 cm 3 to 1.2 cm 3 per gram of the solidified porous carbon material; pulverizing the solidified porous carbon material; A method for producing a pulverized product of a solidified porous carbon material.
Citation Information
Patent Citations
Preparation of low density porous carbon granule
JP1991223105A
Adsorbent for adsorbing volatile organic compound, its producing method and method for utilizing bark or its molding
JP2009226401A
Decontaminant, carbon / polymer composite, decontamination sheet member and filter material
JP2012179589A
Hollow activated carbon
JP2012180273A
Adsorbent, carbon / polymer composite and adsorptive sheet adsorbing virus and / or bacterium
JP2012187571A